Alpha-Thalassemia X-Linked Intellectual Disability Syndrome in a Boy with a Strong Family History of Smith–Lemli–Opitz's Syndrome - Jafar, Bedour; Sharma, Kamal P.; Maertens, Paul (Journal of Pediatric Neurology, 2024)
Alpha-thalassemia X-linked intellectual disability (ATRX) syndrome is a rare disorder characterized by facial dysmorphism, genitourinary tract abnormalities, alpha-thalassemia, and cognitive impairment. Patients present in early infancy with hypotonia, microcephaly, failure to thrive, and delayed milestones. We report a boy with strong family history of the Smith–Lemli–Opitz's syndrome (SLOS) phenotype. All affected family members displayed facial features and presentation identical to those of our patient. None had hypocholesterolemia. All affected family members were boys and have died. Molecular genetic testing in our patient revealed a likely pathogenic mutation in the X-linked recessive ATRX gene. We conclude that SLOS and ATRX syndrome are uncommon disorders sharing similar manifestations. Awareness of such similarity should prompt physicians to explore the possibility of ATRX syndrome in relatives of patients with unproven SLOS.
Keywords: alpha-thalassemia X-linked intellectual disability; hypotonia; intestinal dysmotility